2022
DOI: 10.1097/bot.0000000000002259
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Surgical Site Infections in OTA/AO Type C Tibial Plateau and Tibial Plafond Fractures: A Systematic Review and Meta-Analysis

Abstract: ScienceDirect, and the Cochrane Library, were used in our systematic literature search. Search results were restricted to articles transcribed in English/Spanish and publication date after January 1, 2000, to present day.Study Selection: Inclusion criteria were studies reporting postoperative infection data for OTA/AO type 41C, 43C, or equivalent fractures of skeletally mature individuals. A minimum of 6 total fractures of interest and a frequency of 75% overall were required. Studies reporting on pathologic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…A recent systematic review of 3158 type 43C fractures reported an overall 9.1% deep infection rate, though did not stratify for acute versus staged fixation, and significant heterogeneity existed between included publications (I 2 = 0.55). 18 The results of this study parallel the results of more recent literature and systematic reviews. In this study, we report an overall deep infection rate of 9.2%, with 8.6% and 10% rates in staged versus acute fixation (P = 0.99).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A recent systematic review of 3158 type 43C fractures reported an overall 9.1% deep infection rate, though did not stratify for acute versus staged fixation, and significant heterogeneity existed between included publications (I 2 = 0.55). 18 The results of this study parallel the results of more recent literature and systematic reviews. In this study, we report an overall deep infection rate of 9.2%, with 8.6% and 10% rates in staged versus acute fixation (P = 0.99).…”
Section: Discussionsupporting
confidence: 85%
“…A recent systematic review of 3158 type 43C fractures reported an overall 9.1% deep infection rate, though did not stratify for acute versus staged fixation, and significant heterogeneity existed between included publications (I 2 = 0.55). 18…”
Section: Discussionmentioning
confidence: 99%
“…In 2000 patients treated with ORIF by henkelman et al in 2020, the rate of surgical site infection was 4.7% (93/2000) (56). In 2022, the rate of deep infection in OTA/AO type C tibial plateau reported by Bullock et al was 6% (57).…”
Section: Infectionmentioning
confidence: 99%
“…A recently published systematic review and meta-analysis of 182 published studies estimated the overall incidence of postoperative infection to be 15% with a 95% confidence interval of 13%-17%. 27 Thus, a baseline infection rate of 15% was assumed for calculation of cost savings for our health economic model. In addition, a second health economic model with a more conservative 13% SSI rate as a reference was created.…”
Section: Statistical Analysis and Health Economic Modelmentioning
confidence: 99%
“…Using this incremental cost of infection treatment, the additional cost of infection treatment per patient was calculated using the respective infection rates of 7.4% in the iNPWT group from this study, versus 13%, 15%, 17%, which were assumed for patients without iNPWT, based on the systematic review and meta-analysis of 182 studies. 27 The cost of iNPWT was estimated using the average contract price of $495 for a 3M Prevena Peel and Place System Kit (3M). Categorical variables were compared using x 2 or Fisher exact tests.…”
Section: Statistical Analysis and Health Economic Modelmentioning
confidence: 99%